1999
DOI: 10.1038/sj.onc.1202916
|View full text |Cite
|
Sign up to set email alerts
|

Distinction between AP1 and NF-E2 factor-binding at specific chromatin regions in mammalian cells

Abstract: Speci®c nuclear factor-DNA complexes formed within the promoters and enhancers are essential for transcriptional regulation. For eukaryotic systems, however, some DNA motif(s) are capable of binding to a family of related factors, thus making it di cult to identify the factor actually binding on the chromatic DNA in vivo and modulating the local transcription processes. To resolve this matter, we have re®ned a chromatin immunoprecipitation assay. Using the assay, we could directly link the regulatory functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…NF-E2 interacts not only with the LCR (Daftari et al 1999;Forsberg et al 2000;Sawado et al 2001), but also with the promoter region, even though no canonical NF- E2 binding sites are present in the promoter (Sawado et al 2001). Previously, we proposed two models for sequence-independent NF-E2 recruitment to the promoter: NF-E2 may be recruited to the promoter via interaction between the LCR and the promoter; alternatively, NF-E2 may reside in two independent protein complexes that bind to the LCR and the active promoters (Sawado et al 2001).…”
Section: Nf-e2 and Pol II Recruitment To The ␤-Globin Promoter Are Lcmentioning
confidence: 99%
“…NF-E2 interacts not only with the LCR (Daftari et al 1999;Forsberg et al 2000;Sawado et al 2001), but also with the promoter region, even though no canonical NF- E2 binding sites are present in the promoter (Sawado et al 2001). Previously, we proposed two models for sequence-independent NF-E2 recruitment to the promoter: NF-E2 may be recruited to the promoter via interaction between the LCR and the promoter; alternatively, NF-E2 may reside in two independent protein complexes that bind to the LCR and the active promoters (Sawado et al 2001).…”
Section: Nf-e2 and Pol II Recruitment To The ␤-Globin Promoter Are Lcmentioning
confidence: 99%
“…Targeted disruption of the p45/NF-E2 gene in mice revealed that NF-E2 is required for megakaryopoiesis (40), whereas studies in p45/ NF-E2-null CB3 erythroleukemia cells revealed an important role in activating ␤-globin transcription (32,33,41,42). We used complementation analysis in CB3 cells to show that NF-E2 establishes a component of the histone modification pattern of the murine ␤-globin locus.…”
mentioning
confidence: 99%
“…Endogenous p45/NF-E2 occupies the LCR, and to a lesser extent, the bmajor promoter in erythroid cells (Daftari et al, 1999;Forsberg et al, 2000a;Johnson et al, 2001;Sawado et al, 2001;Im et al, 2005). The finding that Pol II occupies the LCR, but not the bmajor promoter, and p45/NF-E2 expression rescues Pol II occupancy at the promoter in CB3 cells, led to the model that p45/NF-E2 induces long-range Pol II transfer, resulting in considerably more Pol II at the promoter and transcriptional activation (Johnson et al, 2001).…”
Section: P45/nf-e2mentioning
confidence: 99%